Effects of Emergent Literacy Interventions for Preschoolers With Autism Spectrum Disorder. (October 2017) - Hudson, Roxanne F.; Sanders, Elizabeth A.; Greenway, Rosanne; Xie, Sharon; Smith, Maya; Gasamis, Colin; Martini, Jay; Schwartz, Ilene; Hackett, Jacob
Combining data from a series of three planned consecutive randomized controlled trials, the present study investigates two literacy interventions for preschool children with autism spectrum disorder. For the first cohort, children were randomized to interactive book reading (IBR; treatment) or business as usual (BAU; control); in Cohort 2, children were randomized to phonological awareness (PA; treatment) or BAU; in Cohort 3, children were randomized to IBR or PA. Both treatments were implemented weekly in the classroom from November to May. Combined across cohorts, data from 57 classrooms in 8 districts were available for analysis ( n = 47, IBR; n = 42, PA; n = 44, BAU). Model results showed that IBR had significantly greater pretest-posttest gains than the sample mean on expressive vocabulary and listening comprehension (approximate effect sizes: d* = 0.29 and 0.30), whereas PA had significantly greater PA gains ( d* = 0.39).